Human Suffering: An Integrative Literature Review - Duarte Quilao, Teodora (Cultura del cuidado, 2018)
Abstract Introduction: Suffering is a universal multifaceted phenomenon hard to define and often connected to pain. Suffering is not a homogeneous concept. Instead, suffering is a diffused term that includes innumerable ways of dealing with depression, pain, loss, and adversity. Suffering is described as a response or behavior recognized by introspection or observation of the behavior of the person and his/her environment. Objective: The purpose of this article is to describe the role of the advanced nurse practitioners when dealing with the construct of suffering and to present a review of literature related to the human suffering experience. Methods: The CINAHL Complete, PubMed, One Search, MEDLINE, PsychInfo, ProQuest Dissertation and Theses Global databases were search using the keywords suffering, experiences, meanings and perceptions of suffering. Search limits included peer-reviewed articles published in the English language from 1980 to 2016. Results: A total of nine qualitative and five quantitative studies were reviewed. Three major themes were identified: the dimensions of suffering (physical, psychological, social, existential and ethical), enduring suffering and measuring human suffering, and perceiving another’s suffering by using reliable and valid instruments.